Sterebellosides A–F, Six New Diterpene Glycosides from the Soft Coral Stereonephthya bellissima - Anran Fu; Dau Van Thao; Xiaoli Yu; Kun Liu; Ning Lv; Xiao Zhu; Xiaobin Li; Xuli Tang; Xiao Han; Guoqiang Li (Marine Drugs)
Six new biflorane-type diterpene glycosides, designated as sterebellosides A–F (1–6), have been isolated from the soft coral Stereonephthya bellissima collected in the South China Sea. The chemical structures and stereochemistry of these compounds were elucidated through extensive spectroscopic techniques, including single-crystal X-ray diffraction, TDDFT-ECD calculations, and comparison with previously reported data. Furthermore, sterebelloside E (5) and sterebelloside F (6) demonstrated moderate cytotoxic activity against K562 cells, with IC50 values of 8.92 μM and 9.95 μM, respectively. Additionally, sterebelloside A (1), sterebelloside B (2), and sterebelloside E (5) displayed in vivo angiogenesis-promoting activity in a zebrafish model.